2011
DOI: 10.1016/j.cardfail.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Three Gram Sodium Intake is Associated With Longer Event-Free Survival Only in Patients With Advanced Heart Failure

Abstract: Background There is limited evidence to support the recommendation that patients with heart failure (HF) restrict sodium intake. The purpose of this study was to compare differences in cardiac event-free survival between patients with sodium intake above and below 3g. Methods A total of 302 patients with HF (67% male, 62±12 years, 54% New York Heart Association [NYHA] class III/IV, ejection fraction 34 ± 14%) collected a 24-hour urine sodium (UNa) to indicate sodium intake. Patients were divided into 2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 23 publications
8
98
0
3
Order By: Relevance
“…20, 45 Arcand and colleagues 45 showed that in a HF cohort consisting mostly of patients with NYHA class I to II symptoms, Ն2800 mg/d sodium resulted in more HF hospitalizations in comparison with those on lower intake. Lennie and colleagues 20 interestingly showed Ͻ3000 mg/d sodium was associated with better outcomes in NYHA class III to IV patients, whereas it was associated with significant increase in hospital visits, readmissions, and mortality in NYHA class I to II patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20, 45 Arcand and colleagues 45 showed that in a HF cohort consisting mostly of patients with NYHA class I to II symptoms, Ն2800 mg/d sodium resulted in more HF hospitalizations in comparison with those on lower intake. Lennie and colleagues 20 interestingly showed Ͻ3000 mg/d sodium was associated with better outcomes in NYHA class III to IV patients, whereas it was associated with significant increase in hospital visits, readmissions, and mortality in NYHA class I to II patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Congruent with this observation, a recent study reported that only 34% of patients consume Ͻ3000 mg and only 15% consume Ͻ2000 mg sodium daily based on their 24-hour urinary sodium excretion. 20 Sodium consumption Ͻ2000 mg/d is difficult to achieve even with dietician education, 21 and studies have demonstrated that sex 22 and race 23 affect dietary preferences and adherence to sodium restriction recommendations in patients with HF.…”
Section: Sodium Intake Recommendations and Patternsmentioning
confidence: 99%
“…With patient or family assistance, hospital discharge and other medical records were obtained from identified sources of care outside of the study‐site healthcare systems. We have >20 years of experience collecting these data and have successfully obtained hospitalization data on all rural patients in our current and previous studies 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41. All‐cause mortality data (date and cause of death) were collected for 1 year from baseline by a combination of medical record review, electronic clinical record review, interviews with patients’ healthcare providers and family, and public death record review 30, 31, 40, 41, 42, 43…”
Section: Methodsmentioning
confidence: 99%
“…When quality assurance information related to urine collection was provided, it was often quite limited. Only 5 of the 9 included studies reported quality assurance procedures or excluded participants on the basis of incomplete collections, 47,54,57,60,66 and 1 excluded incomplete collections in a sensitivity analysis. 69 Exclusions in these studies ranged from <1% to 11% compared with the 20% to 25% reported in studies that used PABA (p-aminobenzoic acid) testing 28 (onlineonly Data Supplement Table 2a).…”
Section: Menmentioning
confidence: 99%